2014
DOI: 10.1002/prep.201400020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fuel Particle Size on Flame Propagation Velocity in Thermites with a Nanoscale Oxidizer

Abstract: The effect of aluminum size on confined flame propagation velocities in thermite composites was investigated between 108 μm and 80 nm, and in all cases using nanometric copper oxide as the oxidizer. It was found that the velocity exhibited two distinct regimes; between 108 and 3.5 μm the velocity scaled as the particle diameter to the − 0.56 power, and becomes invariant of size below this. One explanation for the invariance is that the pressure‐driven flow reaches some peak velocity, controlled by the pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Though mixing methods that achieve the intimate mixing of nano-dimensional fuel and oxidant in solvents are commonly used to produce nanothermites (Perry et al 2004;Puszynski, Bichay, and Swiatkiewicza 2010;Nellums et al 2013), the arrestive reactive milling of larger particles , solgel oxide synthesis (Tillotson et al 2001), and more complex methods that afford specific fueloxidant architectures are known (Shende et al 2008;Bahrami et al 2014). Many aspects of the nanoaluminum thermite reaction have been studied in detail, including aluminum melting and dispersion mechanisms (Levitas, Pantoya, and Dikici 2006;Firmansyah et al 2012;Jian, Piekiel, and Zachariah 2012), burning rate parameters (Asay et al 2004;Perry et al 2004;Yarrington et al 2011;Sullivan, Kuntz, and Gash 2014), and ignition methods (Pantoya and Granier 2005;Petre et al 2014;Shaw et al 2014). The current state of knowledge with regard to nano-aluminum production, oxidation, and thermite reaction has been recently reviewed (Rossi 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Though mixing methods that achieve the intimate mixing of nano-dimensional fuel and oxidant in solvents are commonly used to produce nanothermites (Perry et al 2004;Puszynski, Bichay, and Swiatkiewicza 2010;Nellums et al 2013), the arrestive reactive milling of larger particles , solgel oxide synthesis (Tillotson et al 2001), and more complex methods that afford specific fueloxidant architectures are known (Shende et al 2008;Bahrami et al 2014). Many aspects of the nanoaluminum thermite reaction have been studied in detail, including aluminum melting and dispersion mechanisms (Levitas, Pantoya, and Dikici 2006;Firmansyah et al 2012;Jian, Piekiel, and Zachariah 2012), burning rate parameters (Asay et al 2004;Perry et al 2004;Yarrington et al 2011;Sullivan, Kuntz, and Gash 2014), and ignition methods (Pantoya and Granier 2005;Petre et al 2014;Shaw et al 2014). The current state of knowledge with regard to nano-aluminum production, oxidation, and thermite reaction has been recently reviewed (Rossi 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using nanometric Al, a larger size of 3.5 mm was used (H-2, Valimet corp.). Past work has shown that the dimensions of the fuel are less important than the dimensions of the oxidizer [4], and this was verified in a recent article by Sullivan et al [16], where it was found that micrometer-sized Al reacted as well, if not better than nano-sized Al, so long as the oxidizer was kept nanometric. Nano-Al has a much higher percentage of Al 2 O 3 from the passivation shell, is aggregated in morphology, and may have adsorbed organic species present on the surface.…”
Section: Sample Preparation and Velocity Measurementsmentioning
confidence: 81%
“…More recently, Sullivan et al have prepared Al/CuO thermites by acoustic mixing, from nano-sized copper oxide and aluminum powders (0.08-108 mm). According to these authors, RAM is more appropriate than ultrasonication for mixing a nanopowder with a micrometer-sized powder, to avoid the segregation of the components [73]. On the other hand, Hope et al have obtained explosive core-shell particles or co-crystals by this technique.…”
Section: Resonant Acoustic Mixing (Ram)mentioning
confidence: 99%